2013
DOI: 10.1007/s10456-013-9401-6
|View full text |Cite
|
Sign up to set email alerts
|

Heparan sulfate in angiogenesis: a target for therapy

Abstract: Heparan sulfate (HS), a long linear polysaccharide of alternating disaccharide residues, interacts with a wide variety of proteins, including many angiogenic factors. The involvement of HS in signaling of pro-angiogenic factors (e.g. vascular endothelial growth factor and fibroblast growth factor 2), as well as interaction with anti-angiogenic factors (e.g. endostatin), warrants its role as an important modifier of (tumor) angiogenesis. This review summarizes our current understanding of the role of HS in angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 265 publications
0
49
0
Order By: Relevance
“…Since 3-OS HS facilitates HCMV infection, its further potential in overall disease development, especially in immune modulation or angiogenesis, can be further investigated using corneal endothelial cells (42). Several lines of evidence already suggest that sulfated HS plays a critical role during multiple pathophysiological processes, including inflammation and vascular angiogenesis (43)(44)(45). Our study provides a unique example of a naturally susceptible cell type that HCMV targets.…”
Section: Expression Of 3-ost Enzymes In His Cells Enhances Fusion Witmentioning
confidence: 87%
“…Since 3-OS HS facilitates HCMV infection, its further potential in overall disease development, especially in immune modulation or angiogenesis, can be further investigated using corneal endothelial cells (42). Several lines of evidence already suggest that sulfated HS plays a critical role during multiple pathophysiological processes, including inflammation and vascular angiogenesis (43)(44)(45). Our study provides a unique example of a naturally susceptible cell type that HCMV targets.…”
Section: Expression Of 3-ost Enzymes In His Cells Enhances Fusion Witmentioning
confidence: 87%
“…Thus, it is evident why this enzyme may be an effective and attractive drug target. 32 , 35 Several HPSE inhibitors have been developed, and some of them have undergone clinical trials showing efficacy against tumors. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Preclinical and clinical studies have demonstrated that therapies targeting the HPSE/SDC1 axis hold promise for blocking the aggressive behavior of cancer. 16 , 35 SDC1 plays a crucial role in carcinogenesis and is an attractive target for anticancer treatment with HPSE inhibitors and immunotherapy with anti-SDC1 antibodies. 17 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…For example, 6‐ O ‐sulfated CS disaccharides are increased up to 50‐fold in gastrointestinal carcinoma (4), and 6‐ O ‐sulfated and 4‐ O ‐, 6‐ O ‐disulfated CS structures are elevated in ovarian cancer (5, 6). Furthermore, HS 6‐ O sulfation is of significant importance in fibroblast growth factor (FGF)‐2/vascular endothelial growth factor (VEGF) signaling (7) and (tumor) angiogenesis (8), and silencing of HS 6‐ O ‐sulfotransferase‐2 inhibits angiogenesis and tumorigenesis in mice (9, 10). These effects underscore the need for compounds that can interfere with GAG function, biosynthesis, and specific sulfation.…”
Section: Introductionmentioning
confidence: 99%